One health approach in the fight against yellow fever in Nigeria - Seyi Enitan; Daniel Gbise; Banenat Dogonyaro; Samuel Eke; Unata Iduh; Michael Dada; Olaitan Adebola; Osakue Osareniro; Grace John-Ugwuanya; Grace Itodo; Richard Akele; Okeoghene Edafetanure-Ibeh; et al. (Microbes and Infectious Diseases)
Background:  Yellow fever (YF) remains a significant public health concern in Nigeria, with sporadic outbreaks causing considerable morbidity and mortality. This zoonotic viral disease is transmitted primarily by Aedes mosquitoes, posing a constant threat to human populations. Although vaccination efforts have been ongoing for years, outbreaks still occur, underscoring the need for a comprehensive approach to combat YF. In Nigeria, adopting a One Health approach is imperative for effective yellow fever control. This approach recognizes the intricate interplay between human health, animal health, and the environment. Key strategies include the implementation of travel advisories, widespread vaccination campaigns, and early detection and reporting of cases. Surveillance efforts extend to both human and non-human primate populations to monitor the circulation of the virus accurately. Community engagement plays a vital role in this approach, with local communities actively participating in efforts to eliminate mosquito breeding sites. Integrated mosquito management techniques, such as the use of insecticides and repellents, are promoted alongside community-led interventions to reduce breeding grounds, such as removing stagnant water. By embracing the principles of One Health and implementing coordinated efforts across regions within Nigeria, we can strive towards the eradication of yellow fever. This holistic approach holds the potential to mitigate the burden of disease and pave the way for a future free from the threat of yellow fever outbreaks in Nigeria.